Hyponatraemia in imported malaria is common and associated with disease severity - van Wolfswinkel, Marlies E (BioMed Central, 2010)
BACKGROUND: Hyponatraemia (serum sodium < 135 mmol/L) has long been recognized as a complication of malaria. However, few studies have been done in non-immune adult populations. It has not been investigated previously how hyponatraemia is distributed among the various Plasmodium species, and its association with malaria severity is unknown. The aim of this retrospective cohort study was to determine the prevalence of hyponatraemia and its association with malaria severity in a large cohort of patients with imported malaria caused by various Plasmodium species. METHODS: All patients that were diagnosed with malaria in the Harbour Hospital and Institute for Tropical Diseases in Rotterdam in the period 1999-2009 and who had available serum sodium on admission were included. Severe malaria was defined according to the modified WHO criteria. Prevalence of hyponatraemia and its association with malaria severity were investigated by univariate comparison, ROC analysis and multivariate logistic regression analysis. RESULTS: A total of 446 patients with malaria (severe falciparum malaria n = 35, non-severe falciparum malaria n = 280, non-falciparum malaria n = 131) was included. Hyponatraemia was present in 207 patients (46%). Prevalence and severity of hyponatraemia were greatest in severe falciparum malaria (77%, median serum sodium 129 mmol/L), followed by non-severe falciparum malaria (48%, median serum sodium 131 mmol/L), and non-falciparum malaria (34%, median serum sodium 132 mmol/L). Admission serum sodium < 133 mmol/L had a sensitivity of 0.69 and a specificity of 0.76 for predicting severe malaria. Multivariate logistic regression showed that serum sodium < 131 mmol/L was independently associated with severe falciparum malaria (odds ratio 10.4, 95% confidence interval 3.1-34.9). In patients with hyponatraemia, hypovolaemia did not appear to play a significant role in the development of hyponatraemia when prerenal azotaemia and haematocrit were considered as surrogate markers for hypovolaemia. CONCLUSIONS: Hyponatraemia is common in imported malaria and is associated with severe falciparum malaria. From a clinical point of view, the predictive power of hyponatraemia for severe malaria is limited. The precise pathophysiological mechanisms of hyponatraemia in malaria require further study.